Upaya Meningkatkan Kualitas Pembelajaran IPAS Melalui Model Quantum Teaching Berbantuan Media Grafis Pada Siswa Kelas V SD 1 Mijen - Mudrikatussyifa, Mudrikatussyifa; Fakhriyah, Fina; Purbasari, Imaniar (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to describe the application of the Quantum Teaching model assisted by graphic media to improve teacher teaching skills, student learning activities and learning outcomes in science learning. This classroom action research was carried out in 2 cycles in class V of SD 1 Mijen with research subjects totaling 34 students. Data collection techniques are carried out through observation, interviews, tests and documentation. Quantitative data analysis techniques, descriptive statistics and qualitative descriptive. The research results showed that teachers' teaching skills increased in cycle I by obtaining a percentage of 74% with good qualifications and increased in cycle II with a percentage of 90% with very good qualifications. Student learning activities in cycle 1 obtained a percentage of 68% with good qualifications and increased in cycle II to obtain a percentage of 80% with good qualifications. Student learning outcomes in cycle I obtained classical completeness of 59% and increased in cycle II with classical completeness reaching 82%. It can be concluded that the application of the Quantum Teaching learning model assisted by graphic media in science and science learning can improve teacher teaching skills, student learning activities and learning outcomes for class V students at SD 1 Mijen.